2016
DOI: 10.1016/j.orggeochem.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Intact polar diacylglycerol biomarker lipids isolated from suspended particulate organic matter accumulating in an ultraoligotrophic water column

Abstract: Intact polar diacylglycerols (IP-DAGs) are essential components of cell membranes. Because they are structurally diverse and hypothesized to represent primarily living cells, they are potential molecular markers for a recent contribution by microbial communities to various carbon reservoirs. This study employed a novel molecular networking approach to investigate the evolution of IP-DAG structural diversity with depth in an ultraoligotrophic environment of the western South Pacific Ocean to test the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 70 publications
2
18
0
Order By: Relevance
“…avg. = 30.4 ± 0.7; Figures 4A, 5) and saturated compared to those described in the surface equatorial N. Pacific (Van Mooy and Fredricks, 2010) or produced in algal cultures (Kato et al, 1996), including picoeukaryotes (Kharbush et al, 2016). The absence of the long chain C 22:6 fatty acid further discounts a eukaryotic source of PC (cf.…”
Section: Ipl Taxonomic Source Indicationsmentioning
confidence: 66%
See 3 more Smart Citations
“…avg. = 30.4 ± 0.7; Figures 4A, 5) and saturated compared to those described in the surface equatorial N. Pacific (Van Mooy and Fredricks, 2010) or produced in algal cultures (Kato et al, 1996), including picoeukaryotes (Kharbush et al, 2016). The absence of the long chain C 22:6 fatty acid further discounts a eukaryotic source of PC (cf.…”
Section: Ipl Taxonomic Source Indicationsmentioning
confidence: 66%
“…same filters (Brandsma et al, 2012;Kharbush et al, 2016). The oligotrophic conditions and relatively lower amounts of biomass in the mesocosms investigated during the current study may thus explain why PG and PE were below the limit of detection.…”
Section: Ipl Taxonomic Source Indicationsmentioning
confidence: 70%
See 2 more Smart Citations
“…Research on the cycling of specific organic compounds through proteomics, metabolomics, lipidomics and the chemical and structural characterization of organic matter represent Emerging areas of Chemical Oceanography. These types of measurements (e.g., Collins et al, 2016;Heal et al, 2017;Kharbush et al, 2016;Kido Soule et al, 2015;Koch et al, 2005;Pearson, 2014;Slattery et al, 2012) may have a solid theoretical basis but their interpretive power is currently limited by the extent of application. For example, marine proteomics studies have revealed physiological responses of Southern Ocean phytoplankton to changing environmental conditions (Boyd et al, 2016), identified combined nutrient stressors in the Pacific Ocean , and been used to track organic nitrogen sources from the water column to sediment burial in the Bering Sea (Moore et al, 2012), demonstrating the field's emerging interpretive power.…”
Section: Fostering Tool and Technique Development In Chemical Oceanogmentioning
confidence: 99%